Champions of charity war and the rise of the Red Cross - Hutchinson, John F. (Westview Press, 1996)
The Red Cross played an especially important role in encouraging the mass involvement of women in the "home front" for the first time. It did this through magazines, postcards, posters, bandage-rolling parties, and speeches that blended romantic images of humanitarianism and war into a unique brand of maternal militarism. A true pioneer in mass propaganda, the Red Cross taught millions that preparation for war was not just a patriotic duty but a normal and desirable social activity. The Red Cross societies had proven their usefulness in mobilizing civilians in wartime, and most of their functions were taken over by government agencies by the time of World War II. Gradually the Red Cross became better known for its work in public health, disaster relief, and lifesaving classes. But the legacy of a darker past still lingers: the red cross on a white background found on army ambulances, or the unsubtle subtext of sacrifice and heroism in Red Cross television advertising